Perception towards gold investment a case in Negeri Sembilan / Nur Afiqah Mohd Youssof - Mohd Youssof, Nur Afiqah (Faculty of Business Management, 2016)
Gold is often regarded as a good hedge against currency depreciation and other economic and political events (Leung & Ward, 2015). Besides, gold is a good value keeper where it can be kept for future use (Nik Muhammad, 2011). Nowadays, gold has been as an instrument for investment in Malaysia. The issue related to gold investment is the status of investment regarding to shariah compliant or not. The objective for this research is to identify public knowledgeability towards gold investment. The independent variables involve in this research are knowledge of public towards gold investment, gold investment is a stable and secure investment and as another option in diversifying investment risk. The sample for this research is public respondents by using simple random sampling. This research will be conducted by using primary data in order to get the information and achieved the objective. The data will be collected from distribution of questionnaires. The data will be run by using SPSS